University Learning Management System: A Promising Solution to Improve Students’ English Ability in Large English Classes - Dinovia Fannil Kher; Yati Aisya Rani (STAI Hubbulwathan Duri, 2022)
The covid-19significantly shifted the trend in teaching. University Learning Management System, often known as e-learning was believed to be the form of future education. One of the solutions offered was that its various features utilize the need to manage to teach large English classes. The design of the research was casual-comparative research where two groups were compared based on their mean score of the four tests. They were the first and second quiz scores, the scores of students’ mid-semester exams, and their final scores. The first group studied consisted of 50 students taught using the old normal way, while the other group consisted of 50 students also studied by utilizing the availability of their online learning platform or the university LMS. The data were analyzed using parametric statistic, since the data distribution was normal, then independent t test was applied. The data were used to answer the hypothesis whether or not there was a significant difference between the two groups. The research findings showed that the significant two-tailed independent test was lower than the 0.05 alpha significant, therefore, it was concluded that there was significant different between the two groups. Shortly, learning management system was the alternative to manage large English classes at universities, that worked on improving students’ English ability.